Paracoccidioidomicose: estudo experimental em Calomys callosus - Berbert, Alceu Luiz Camargo Villela (2010)
Paracoccidioidomycosis is one of the most prevalent systemic mycosis in Latin America, including Brazil. It is caused by chronic infection with Paracoccidioides brasiliensis, a thermally dimorphic fungus. Calomys callosus, Rengger 1830 (Rodentia, Cricetidae), is a wild rodent found in Central Brazil and has been shown to be susceptible to experimental infection with P. brasiliensis. The objective of this work was to study the clinicopathological aspects of this experimental infection in Calomys. callosus infected with 0.6 x 105 yeast isolated from P. brasiliensis (strain Pb18) and to compare it with two others susceptible animals: A / Sn and B10.A mice. For this, five animals from each group were sacrificed at 7, 15, 30, 60, 90 and 120 days post inoculation (d.p.i.). Samples of the lung, liver and spleen were processed for mycological examination to determine the number of counts of colony forming units (CFU) as well as for histopathological examination using hematoxilyn and eosin (H&E), reticulin Gomori, trichromic (Masson), and Grocott´s stains. Blood samples from each mice were collected from orbital venous plexus and used to detect IgG and IgM specific anti-P. brasiliensis by ELISA. To determine of survival post-infection, others eight animals from each group was used. The mortality rate was higher in C. callosus than A / Sn and B10.A mice, being all deaths occurring up to 118 d.p.i. IgM levels tended to rise in all groups, but in B10.A mice and Calomys callosus groups, the level of IgG was significantly elevated during the all experimental period. Granulomatous lesions were observed in the roots of all animal groups and all granulomas were composed by Langhans giant cells, epithelioid cells, macrophages, lymphocytes, plasma cells, eosinophils, and necrosis. In C. callosus, the development of granulomas in lung was observed with 15 d.p.i. and exhibited extensive necrosis, especially at the end of the experiment. The presence of granulomas in liver was detected with seven d.p.i. in all animals, but the extensive necrosis was observed especially in samples of Calomys callosus. Similar pattern was also observed in spleen samples. In addition, in Calomys callosus the granulomatous lesions were more extensive in lung and spleen than in liver. The assessment of differential deposition of collagen showed that in Calomys callosus and B10.A the lesions were predominantly composed by collagen type III, although in B10.A animals a predominance of collagen type I was observed without, however, exceed the levels observed for collagen type III at the end of the experiment. On the other hand, the levels of collagen were lower in A / Sn mice than Calomys callosus and B10.A. and, apparently, it was not identified in the lung. On the other hand, in this group was observed a tendency to increase the deposition of collagen type I in the liver at the end of experiment. Callomys callosus showed a higher number of CFU in the three organs studied, especially in the lungs. The proportion of viable fungi in liver, lung and spleen was always higher in Calomys callosus than A / Sn and B10.A and tend to increase in liver and lung during the infection progression with the presence of budding fungi. Conclusions: Ours results indicate that the experimental infection by Paracoccidioides brasiliensis (Pb18) was more aggressive and widespread in Calomys callosus than A/Sn and B10, especially in the lung. So, Calomys callosus can be considered as an alternative animal model in studies of paracoccidioidomycosis infection.